FORMULATION OPTIMIZATION, SCALE UP TECHNIQUE AND STABILITY ANALYSIS OF NAPROXEN LOADED LIPOSPHERES - N, Satheesh Babu; Rajan D, Senthil; L, Prabakaran; Srikanth Meka, Venkata; P.C, Suriyakala (Asian Journal of Pharmaceutical and Clinical Research, 2014)
The objective of this research was to formulate the anti-inflammatory drug (naproxen) to provide controlled release and minimizing local side effect by avoiding the drug release in the stomach region. Naproxen was entrapped with lipid-like cetyl alcohol, glyceryl mono stearate and stearic acid using melt dispersion technique. Effect of various formulation and process variables such as concentration of surfactant, concentration of co-surfactant, on formulation parameters such as morphology, entrapment efficiency, and in vitro release of naproxen were studied. The lipospheres were characterized for particle size, photo microscopy, scanning electron microscopy, FT-IR spectroscopy, drug entrapment efficiency, in vitro release studies, and in vitro release kinetics. The shape of microspheres was found to be spherical, drug entrapment efficiency of various batches of microspheres was found to be ranging from 80 to 90 %. The in vitro drug release studies of optimized batches were carried out for up to 24 h using phosphate buffer pH 7.4 showed 80-85% drug release. The optimized formulation batch was considered for scale up process. The lipospheres obtained from the scale up were then characterized for particle size, drug loading and morphology and compared with non-scaled up optimized batch, thereby establishing successful process scale-up.Key words: naproxen, liposphere, scale up technique, optimization, encapsulation efficiency